Relation- ships of neonatal septicemia with the mean serum levels of IL-8 and IL-1 in three large hospitals in Baghdad - Al-Bayaa, Yasmeen J.; Ayoub, Nedhal S. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Neonatal septicemia (NNS) is the most serious complication in Neonatal Intensive Care Units (NICU) that demand urgent diagnosis and accurate treatment. Methods: Serum was obtained from 31 neonates aged 1 hour-28 days that were diagnosed clinically and bacteriologically to have neonatal septicemia. Results: Mean serum levels of both IL-8 and IL-1 recorded a significant increase in neonatal septicemia cases. Conclusion: Usage of IL-8, IL-1 as diagnostic marker for NNS reduces unnecessary antibiotic therapy and therefore unnecessary costs, pain, and possible side effects of antibiotic therapy and it may help to reduce development and spread of drug resistant bacteria.